Unveiling the therapeutic potential of crispr-cas9 technology in the correction of SCD gene mutation - Vincent Weiss (Cellular, Molecular and Biomedical Reports)
Sickle-cell disease is a genetic disorder caused by the substitution of normal hemoglobin with abnormal hemoglobin due to a mutation in the HBB gene. Only a few temporary, symptomatically highly effective treatments are available for this disorder; Therefore, there is a dire need to find more effective treatments with a permanent character. An experiment has been thought out, to edit the mutation in the HBB gene responsible for sickle-cell disease using CRISPR-Cas9 gene editing technology. We purified the HSCs from SCD patients and then used the CRISPR-Cas9 system to edit the HBB gene. The edited cells were assayed for hemoglobin production by HPLC and for mutation status by PCR. We also described functional assays and studies involving preclinical animals to test the efficacy of the edited HSCs. The results from the HPLC and PCR analyses show distinct hemoglobin profiles between healthy individuals and those with SCD. In silico analysis of CRISPR-Cas9 editing of patient HSCs predicts that, following treatment, the normal hemoglobin may increase from 8.2 to 10.2 g/dL. The edited HSCs are predicted to exhibit a gene correction efficiency of 30-50% and give rise to red blood cells with normal morphology and heightened resistance to sickling. The work herein described outlines a transformation in therapeutic potentiation of CRISPR-Cas9 for SCD treatment through the direct action of genetic mutation. Whereas such a technique has shown great promise, further optimization of delivery methodologies, off-target effects, and translation to clinical trials is necessary. Such findings emphasize further research into gene-editing methods applied to the treatment of genetic disorders like SCD.